Towards Efficient Load Balancing BFS on GPUs: One Code for AMD, Intel & Nvidia - Olgu, Kaan; Kenter, Tobias; Nunez-Yanez, Jose; McIntosh-Smith, Simon; Deakin, Tom (Proceedings of the SC '25 Workshops of the International Conference for High Performance Computing, Networking, Storage and Analysis)
Efficient graph processing is essential for a wide range of applications. Scalability and memory access patterns are still a challenge, especially with the Breadth-First Search algorithm. This work focuses on leveraging HPC systems with multiple GPUs available in a single node with peer-to-peer functionality of the Intel oneAPI implementation of SYCL. We propose three GPU-based load-balancing methods: work-group localisation for efficient data access, even workload distribution for higher GPU occupancy, and a hybrid strided-access approach for heuristic balancing. These methods ensure performance, portability, and productivity with a unified codebase. Our proposed methodologies outperform state-of-the-art single-GPU implementations based on CUDA on synthetic RMAT graphs. We analysed BFS performance across NVIDIA A100, Intel Max 1550, and AMD MI300X GPUs, achieving a peak performance of 153.27 GTEPS on an RMAT25-64 graph using 8 GPUs on the NVIDIA A100. Furthermore, our work demonstrates the capability to handle RMAT graphs up to scale 29, achieving superior performance on synthetic graphs and competitive results on real-world datasets.

Time-resolved second-order autocorrelation function of parametric down-conversion - Horoshko, Dmitri B.; Srivastava, Shivang; Sośnicki, Filip Maksymilian; Mikołajczyk, Michał; Karpiński, Michał; Brecht, Benjamin; Kolobov, Mikhail I. (Physical Review A)
We study a possibility of measuring the time-resolved second-order autocorrelation function of one of two beams generated in type-II parametric down-conversion by means of temporal magnification of this beam, bringing its correlation time from the picosecond to the nanosecond scale, which can be resolved by modern photodetectors. We show that such a measurement enables one to infer directly the degree of global coherence of that beam, which is linked by a simple relation to the number of modes characterizing the entanglement between the two generated beams. We illustrate the proposed method by an example of photon pairs generated in a periodically poled potassium titanyl phosphate (KTP) crystal with a symmetric group velocity matching for various durations of the pump pulse, resulting in different numbers of modes. Our theoretical model also shows that the magnified double-heralded autocorrelation function of one beam exhibits a local maximum around zero delay time, corresponding to photon bunching at a short time scale.

Otus Supercomputer - Ehtesabi, Sadaf; Hossain, Manoar; Kenter, Tobias; Krawinkel, Andreas; Ostermann, Lukas; Plessl, Christian; Riebler, Heinrich; Rohde, Stefan; Schade, Robert; Schwarz, Michael; Simon, Jens; Winnwa, Nils; et al.
Otus is a high-performance computing cluster that was launched in 2025 and is operated by the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. The system is part of the National High Performance Computing (NHR) initiative. Otus complements the previous supercomputer Noctua 2, offering approximately twice the computing power while retaining the three node types that were characteristic of Noctua 2: 1) CPU compute nodes with different memory capacities, 2) high-end GPU nodes, and 3) HPC-grade FPGA nodes. On the Top500 list, which ranks the 500 most powerful supercomputers in the world, Otus is in position 164 with the CPU partition and in position 255 with the GPU partition (June 2025). On the Green500 list, ranking the 500 most energy-efficient supercomputers in the world, Otus is in position 5 with the GPU partition (June 2025). This article provides a comprehensive overview of the system in terms of its hardware, software, system integration, and its overall integration into the data center building to ensure energy-efficient operation. The article aims to provide unique insights for scientists using the system and for other centers operating HPC clusters. The article will be continuously updated to reflect the latest system setup and measurements.
Keywords: Otus; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing; Noctua 2; HPC

Software-supported decision support for the foresighted planning of digital business models - Gräßler, Iris; Tusek, Alena Marie (AHFE International)
To remain competitive, companies must continuously adapt their value proposition, especially in response to increasing demands for sustainability and digitalisation. Small and medium-sized enterprises often struggle to implement future-oriented digital business models. The aim is to develop decision support to help companies plan ahead and assess their value proposition, with a focus on foresighted planning. Based on literature research, expert interviews and the analysis of existing solutions, an understanding of “sustainable value” and requirements of decision support are defined. Decision support is implemented in a software. The main contribution is the setup of functions and content such as a list of influence factors, analysing influences and evaluating ideas, control questions and support for the implementation of digital business models. Validation through expert interviews and workshops in mechanical and plant engineering shows that the software supports enterprises in foresighted planning of value proposition and the selection of a concept for digital business models. It makes them robust towards the variety of future scenarios.

„Ich mache mir die Welt, wie sie mir gefällt.“ Jona und Yūnus in Kinderbibel, Kinderkoran und interreligiösen Lesebüchern - Kamcili-Yildiz, Naciye; Keuchen, Marion (Was hat das mit mir zu tun? Zugänge zur Tradition in der islamischen Religionspädagogik)

Zwischen Supermarktkasse und Anwaltskanzlei. Eine klassismuskritische Perspektive auf die Darstellung von Muslim:innen in evangelischen Religionsbüchern - Kamcili-Yildiz, Naciye; Keuchen, Marion (theo web. Zeitschrift für Religionspädagogik. Selig sind die Besitzlosen?!)
Der Beitrag nimmt die Darstellung muslimischer Menschen in evangelischen Religionsbüchern der Jahrgangsstufen 7/8 in den Blick und untersucht sie aus klassismuskritischer Perspektive. Im Zentrum steht die Frage, welche religiösen und sozialen Deutungsmuster in Wort und Bild vermittelt und wie diese didaktisch gerahmt werden. Die Analyse verbindet schulbuchdidaktische und gesellschaftskritische Zugänge, indem sie Karlo Meyers Konzept des „doppelten Individuenrekurses“ mit einem klassismustheoretischen Ansatz nach Markus Gamper und Annett Kupfer verknüpft. Der Beitrag leistet auch eine intersektionale Reflexion im Blick auf eine interreligiöse Religionsdidaktik und mit der Schulbuchforschung verbunden auch einen Beitrag zu einer politischen Religionspädagogik, die mehrheitsgesellschaftliche Stereotype reflektieren lernt.
Keywords: Islam; Klassismus; Diskriminierung; Schulbuchforschung; Schulbuch; Migration

Children’s Bibles in the Reformation: Martin Luther‘s „Passional“ (1529) and Wendelin Rihel‘s „Leienbibel (1540) - Keuchen, Marion (The Oxford Handbook of the Bible and the Reformation)
Through the Reformation, the Bible and education gained central importance. The Reformation principle that the Bible as Holy Scripture should be the only basis and norm for faith (sola Scriptura) emphasized the importance of reading and writing. The Reformers wanted children and laypeople to become independent church members. Teaching material was needed for school lessons, and study Bibles with pictures were produced; Martin Luther’s Little Prayer Book (1529) served as a prototype. The Lay Bible (1540) by Wendelin Rihel was a continuation of Luther’s Little Prayer Book. This innovative period laid the foundation for later children’s Bible traditions.
Keywords: Reformation children’s Bibles; Bible illustrations; lay Bible; passional; Martin Luther; Wendelin Rihel; religious education of children

Consideration of residual stresses and damage in the fracture mechanical investigation of mechanically joined structures - Weiß, Deborah; Duffe, Tobias; Joy, Tintu David; Kullmer, Gunter (Materials Research Proceedings)
Abstract. The process of joining is used in numerous sectors of the manufacturing industry, where constructions composed of individual components or metal sheets are combined to form complex structures. A straightforward and pervasive approach for joining materials of disparate natures and coated surfaces is clinching. During the clinching process, plastic deformation, residual stresses and damage are introduced into the joint. Due to time-varying service loads cracks can initiate and propagate in the vicinity of the joint which limits the lifetime of the clinched structure. In order to prevent those damage cases, it is crucial to perform fracture mechanical evaluation of cracks in the joint region. Therefore, this publication deals with the question of how plastic deformation, residual stresses and damage need to be considered for the assessment of a crack. For this purpose, simple substitute models are employed to illustrate the principles based on the clinching application example.

“I don’t believe that you believe what I believe”: an experiment on misperceptions of social norms and whistleblowing - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina (European Economic Review)

Durch Schulseelsorge Demokratiefähigkeit bilden - Keuchen, Marion; Lindemeyer, Sabine (Rituale und Spiritualität - auch für religiös ungebundene Menschen)

Dankbarkeitskoffer. Schulseelsorge in Hochschule und Schule - Keuchen, Marion

Mut zum Widerspruch. Bibelarbeit auf dem Weg zu Markus 7,24-30 - Fermor, Gotthard; Janssen, Wibke; Keuchen, Marion; Ruddat, David

Social Information Interventions under Competing Norms: Evidence from a Whistleblowing Experiment - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina (SSRN Electronic Journal)

Social Interaction and Feedback-Giving Behavior in the Sharing Economy - An Experimental Analysis - Mir Djawadi, Behnud; Wester, Lisa (SSRN Electronic Journal)

Transfer of powder-based direct coating in the injection molding process from two dimensional components to three-dimensional components - Moritzer, Elmar; Lingnau, Kai Martin (The 40th International Conference of Polymer Processing Society)

Werkstofflicher Ansatz zum adhäsiv-basierten Fügen für hochflexible TPE-Organobleche als Verstärkungsstruktur - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Influence of the processing parameters on the mechanical strenght of injection moulded BMC components for direct screwing - Held, Christian; Moritzer, Elmar (the 40th International Conference of Polymer Processing Society)

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)